SELEKSI KETAHANAN KEKERINGAN BEBERAPA KULTIVAR JAGUNG LOKAL TIMOR PADA FASE PERKECAMBAHAN - Ali Hasan; Theresia Ginting; Mochammad Hasan (Politeknik Pertanian Negeri Kupang, 2017)
The objective of this research is to investagate the level of drought resistance of some local corn cultivars from Timor in the germination phase. The single factor study is the genotype of maize origin of Timor which consists of 22 cultivars. The study was arranged in a complete randomized design (RAL) and repeated 3 times. The observed variables were germination (DB) expressed in% and normal dried germination weight (BKKN), expressed in grams. The analysis of heritability values (h2) was measured by comparing the genotypes of the various phenotypes (total). The h2 value was greater than 0.5 indicates a genotype diversity of drought resistance. Furthermore, the drought resistance rating based on DB difference (DB aquades-DBPEG) and BKKN aquades - BKKN PEG (BKKN aquades - PEG) difference. The result of the research shows that the calculation of h2 value of 22 East Maize cultivars on DBPEG and BKKNPEG measurements is 0.721 and 0.938, respectively, which means that there is a diversity of drought resistance of 22 cultivars tested. Muke Merah corn cultivars (flowers) Muke White (flowers), White Malacca 1, White Haikesak, White Tastim, and Red Fatumonas (flowers) have good potencial to be used as ingredients in breeding programs to obtain drought tolerant varieties of maize.Â Key Word: Corn, Genotype selection, drought resistance, germination